Local nutrient addition drives plant biodiversity losses but not biotic homogenization in global grasslands - Chen, Qingqing; Blowes, Shane A.; Harpole, William Stanley; Ladouceur, Emma; Borer, Elizabeth T.; MacDougall, Andrew S.; Martina, Jason P.; Bakker, Jonathan D.; Tognetti, Pedro Maximiliano; Seabloom, Eric William; Peri, Pablo Luis; Chase, Jonathan M. (Springer Nature, 2025)
Nutrient enrichment typically causes local plant diversity declines. A common but untested expectation is that nutrient enrichment also reduces variation in nutrient conditions among localities and selects for a smaller pool of species, causing greater diversity declines at larger than local scales and thus biotic homogenization. Here we apply a framework that links changes in species richness across scales to changes in the numbers of spatially restricted and widespread species for a standardized nutrient addition experiment across 72 grasslands on six continents. Overall, we find proportionally similar species loss at local and larger scales, suggesting similar declines of spatially restricted and widespread species, and no biotic homogenization after 4 years and up to 14 years of treatment. These patterns of diversity changes are generally consistent across species groups. Thus, nutrient enrichment poses threats to plant diversity, including for widespread species that are often critical for ecosystem functions.